(3GdCdaGX GdeZQHI HGdCdbGH GdeYQHIs - (3YjSi Hf EHQGgje Hf bJjHIs
(3ChdgG (B:s
(3GKfGA MQa GdgeRg hJbhd efg (B: (3WQbfi CeQ , Cgefi agefi , aCgefi (B: (3Cbdbfi hCMRffi , hgefi (B: (3CPGHfi , ef geeJ GdTMe EPG CPHJg s
(3BNQgG (B:s
(3hefg GdjeGeI , hgj ehVhY , hGSe GeQCI , hgj RQbGA GdjeGeI , hde jJab di Pdc EdG HhVY MQha ef cJGHi GdeDda ai eKdK GdcdGe Je GdcJGH HMeO Gddg s
(3cJGH ai GddZIs
(3Ydi ZQGQ cJGH GdedGMfs
(3dGHf OQjOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs